Pengaruh Penjualan Kamar Melalui Online Travel Agent Terhadap Tingkat Hunian Kamar (Studi Kasus di Kayu Manis Jibaran Privite Estate & Spa Bali) - Sulistyawati , Ni Luh Ketut Sri; Peringgaswari, Anak Agung Gaury (Program Studi Administrasi Perhotelan, 2023)
Tourism is a prominent sector in Indonesia and serves as the largest foreign exchange earner. Bali, in particular, remains a highly popular tourist destination, evident from the continuous growth of hotels in the area. Hotel room bookings can be made through various methods, including online travel agents (OTAs). Kayumanis Jimbaran Private Estate & Spa utilizes OTAs as a primary distribution channel alongside direct bookings, as indicated by sales data from 2019 to 2021. The relationship between room sales through OTAs and room occupancy rates at Kayumanis Jimbaran Private Estate & Spa exhibits fluctuations that contradict the expected pattern. Despite an increase in room occupancy rates in 2020, there was no concurrent rise in the number of room sales through OTAs. This inconsistency suggests an incongruity in the contribution and influence of OTA room sales on room occupancy rates. Consequently, this research aims to investigate the impact of room sales through OTAs on room occupancy rates at the mentioned establishment. Data collection methods employed include interviews and documentation studies. The research employs a simple linear regression analysis technique using the SPSS version 25 program. The analysis results reveal that room sales through OTAs exert a positive and significant influence on the room occupancy rate at Kayumanis Jimbaran Private Estate & Spa, with a sales contribution of 80.6%. The remaining 19.4% is attributed to other factors not examined in the study.